Predictive Role Of C-Reactive Protein (CRP) In Determining The Severity Of Acute Cholecystitis Presenting In The Emergency Department Of A Tertiary Care Hospital - Waris, Hira; Khan, Bilal Irshad; Nazir, Amna; Amir, Asad; Khan, Atif; Ali, Qasim (Journal of Rawalpindi Medical College, 2025)
Objective: This research aims to explore the predictive role of CRP in determining the severity and grading of acute cholecystitis, particularly in our local population presenting to the emergency department. Methods: A Cross-sectional (validation) study was conducted at the Department of Surgery, Holy Family Hospital, Rawalpindi, on 288 patients aged 18 to 70 years who had clinical symptoms suggestive of acute cholecystitis. Baseline CRP levels from blood samples taken at the time of admission were determined. Additional CRP measurements were taken at predefined intervals, such as 24 hours and 48 hours after admission. All patients were subjected to follow-up imaging findings via Histopathology as a gold standard technique. The hospital lab was used for the results of the investigation, i.e CRP. Results: CRP levels sensitivity was (93.30%), specificity (85.32%), PPV (91.26%), NPV (88.57%), and diagnostic accuracy (90.28%) in predicting the severity of the acute cholecystitis, taking histopathology as the gold standard. Conclusion: According to the study's findings, CRP has a good predictive value for assessing the severity and grading of acute cholecystitis and can be used as a diagnostic criterion for the condition